Zmuttgletscher flow velocity, debris cover thickness and ablation measurements during 2017 - Nico Mölg; Tobias Bolch; Andrea Walter; Andreas Vieli (PANGAEA, 2019)
Here we provide in-situ measurements on debris cover thickness on Zmuttgletscher, Switzerland. It is one of the largest heavily debris-covered glaciers in the Alps. We further provide 2 DEMs based on UAV imagery and the respective orthophotos, as well as surface flow velocities derived from the orthophotos by automated feature tracking. Further information can be found in the research paper by Mölg et al. (2019) published in The Cryosphere.
Supplement to: Mölg, N et al. (2019): Unravelling the evolution of Zmuttgletscher and its debris cover since the end of the Littel Ice Age. The Cryosphere, 13(7), 1889-1909, https://doi.org/10.5194/tc-13-1889-2019